The man who knew the life and times of Alan Greenspan - Sebastian Mallaby (London Bloomsbury, 2017)
This is the biography of one of the titans of financial history over the last 50 years. Born in 1926, Alan Greenspan was raised in Manhattan by a single mother and immigrant grandparents during the Great Depression - but by quiet force of intellect, he rose to become a global financial 'maestro'.
Includes bibliographical references and index
Keywords: Greenspan, Alan, 1926-; Board of Governors of the Federal Reserve System (U.S.); Monetary policy -- United States